Adoption of oyster culture by women in Kerala - Immanuel, Sheela (Fishery Technology, 2025)
A study was conducted with the objective of examining the socio economic impact of the technology that was transferred to the women folk through variuos methodologies and to empower these women both socially and economically through the adoption of these technologies. Fisher folk in the coastal belts were identified from selected villages viz., Ayiramthengu(23), Dalavapuram (24) and Azheekal (23)and the technology of edible oyster culture was demonstrated. Data were collected from the women with the help of a structured interview schedule. Data were collected for a period of three months during the year 2002- 03. Percentage analysis was done to categorise them under different groups. The study indicated that group farming appears to be the ideal means for the propagation of oyster culture in this region. Serious constraint faced by these groups were identified and suitable remedial measures suggested to overcome the constraints.